A novel virtual reality application for autonomous assessment of cervical range of motion: development and reliability study - Santos-Paz, Jose Angel; Sánchez-Picot, Álvaro; Rojo, Ana; Martín-Pintado-Zugasti, Aitor; Otero, Abraham; Garcia-Carmona, Rodrigo (PeerJ, 2022)
Background Neck pain, one of the most common musculoskeletal diseases, affects 222 million people worldwide. The cervical range of motion (CROM) is a tool used to assess the neck’s state across three movement axes: flexo-extension, rotation, and lateral flexion. People with neck pain often have a reduced CROM, and they feel pain at the end-range and/or accompany neck movements with compensatory trunk movements. Virtual reality (VR) setups can track the movement of the head and other body parts in order to create the sensation of immersion in the virtual environment. Using this tracking position information, a CROM assessment can be performed using a VR setup that may be carried out autonomously from the user’s home. The objectives of this study were to develop a VR experience that could be used to perform a CROM assessment, and to evaluate the intra-rater and inter-rater reliability of the CROM measures guided by this VR experience. To the best of our knowledge, a study of this type has not been carried out before. Materials & Methods A total of 30 asymptomatic adults were assessed using a VR device (HTC Vive Pro Eye™). Two raters provided support with the VR setup, and the participants were guided by the VR experience as they performed the movements. Each rater tested each subject twice, in random order. In addition to a head-mounted display (HMD), a tracker located on the subject’s back was used to measure trunk compensatory movements. The CROM was estimated using only the HMD position and this measurement was corrected using the tracker data. The mean and standard deviation were calculated to characterize the CROM. To evaluate the reliability, the interclass correlation coefficients (ICC) were calculated for intra-rater and inter-rater analysis. The standard error of measurement and minimum detectable change were also calculated. The usability of the VR system was measured using the Spanish version of the System Usability Scale. Results The mean CROM values in each axis of movement were compatible with those described in the literature. ICC values ranged between 0.86 and 0.96 in the intra-rater analysis and between 0.83 and 0.97 in the inter-rater analysis; these values were between good and excellent. When applying the correction of the trunk movements, both the intra-rater and inter-rater ICC values slightly worsened except in the case of the lateral flexion movement, where they slightly improved. The usability score of the CROM assessment/VR system was 86 points, which is an excellent usability score. Conclusion The reliability of the measurements and the usability of the system indicate that a VR setup can be used to assess CROM. The reliability of the VR setup can be affected by slippage of the HMD or tracker. Both slippage errors are additive, i.e., only when the sum of these two errors is less than the compensatory movement do the measurements improve when considering the tracker data.
Keywords: Cervical range of motion; Virtual reality; Reliability; Compensation movement; Virtual reality applications; Head mounted display; Telemedicine